Development and characterization of a new adsorbent for biomolecule separation: intercalation and adsorption of clavulanic acid in layered double hydroxides. Issue 6 (14th July 2015) - Forte, Marcus Bruno Soares; Taviot‐Guého, Christine; Leroux, Fabrice; Rodrigues, Maria Isabel; Maugeri Filho, Francisco
Abstract: BACKGROUND: A new layered double hydroxide (LDH) material has been developed through a pioneering approach, with the goal of being an alternative adsorbent for the separation of biomolecules, such as clavulanic acid (CA). RESULTS: Zn2 Cr‐CA hybrid LDH assemblies were prepared through a coprecipitation method to evaluate the affinity between the CA molecule and the interlayer sites. The resulting inorganic–organic 'sandwich' structure was characterized by a combination of techniques showing an expansion of the layered structure from 0.78 nm up to values of 2.30 nm upon CA intercalation. Isotherm studies were carried out to evaluate the adsorption capacity of LDH towards CA. The Freundlich adsorption model was found to fit the experimental data well, indicating a relatively large adsorption capacity for the adsorbent Zn2 Cr‐NO3, as high as 73.63, 128.76, and 229.62 mg 1‐ nF L nF g −1 at 20, 30, and 35 °C, respectively. CONCLUSION: Zn2 Cr‐NO3 adsorption capacity was not influenced by the presence of amino acids, thus underlining that it is a LDH composition which may be a suitable alternative for the separation of CA. LDH micro‐particles were additionally encapsulated with calcium alginate gel (LDHME ) and characterized for particle average diameter ( dp = 171 µm), bulk density ( ρbulk = 0.63 g cm −3 ), particle density ( ρp = 2.2 g cm −3 ), particle porosity ( ϵp = 0.71) and bed porosity ( ϵB = 0.40). The application of LDHME in the separation of CA from complex mixtures, containing tyrosine and proline, was considered satisfactory based on purification factors of about 2.32 and degrees of purity higher than 99%. © 2015 Society of Chemical Industry